LINGUOCULTURAL FEATURES OF PHRASEOLOGISMS USED IN K. SULTANOV'S ROMAN “AJINIYAZ” (Journal of Universal Science Research, 2026)
The article analyzes phraseological units in the novel "Ajiniyaz" by K. Sultanov, a prominent representative of Karakalpak literature, from a linguocultural perspective. The connection between language and culture, as well as the transmission of a people's national mentality and ethnographic realities through phraseological units, is scientifically substantiated.